POTENSI AGROFORESTRI UNTUK MENDUKUNG BIOPROSPEKTING - Octavia, Anggi; Winarno, Gunardi Djoko; Iswandaru, Dian; Setiawan, Agus (Universitas Tanjungpura, 2023)
Agroforestry is a land use system that combines forestry and agricultural plants on one land. The many types of plants cultivated on one agroforestry land can support a village if its use is carried out sustainably. One way to use it is to develop bioprospecting activities for plants for medicine, food and cosmetics. The aim of this research is to find out how to optimize agricultural land using an agroforestry system, find out the community's perception of land use using an agroforestry system, and find out the types of plants used to support bioprospecting. This research was conducted in May-June 2023. The research method was carried out by means of surveys, interviews and vegetation analysis. The research results show that the majority of people agree regarding the ecological, economic and socio-cultural benefits resulting from land use into an agroforestry system as a sustainable system. There are several types of plants on agroforestry land that have great potential to be utilized to support bioprospecting. The percentage of plant species that have bioprospecting potential for food is 37%, 37% for medicines and 26% for cosmetic ingredients. Through the development of bioprospecting plants, it is hoped that it will be able to help the community to optimize the use of agricultural land with an agroforestry system.Keywords: Agroforestry, Bioprospecting, Likert ScaleAbstrakAgroforestri merupakan sistem tata guna lahan kombinasi jenis tanaman kehutanan dengan tanaman pertanian dalam satu lahan. Banyaknya jenis tanaman yang dibudidayakan pada satu lahan agroforestri dapat menjadi penunjang desa apabila pemanfaatannya dilakukan secara berkelanjutan. Salah satu cara pemanfaatannya dengan melakukan pengembangan kegiatan bioprospecting tumbuhan untuk obat, pangan, dan kosmetika. Tujuan dari penelitian ini adalah untuk, mengetahui cara pengoptimalisasian lahan pertanian menggunakan sistem agroforestri dan mengetahui pesepsi masyarakat terhadap pemanfaatan lahan menggunakan sistem agroforestri, serta mengetahui jenis tanaman yang dimanfaatkan untuk mendukung bioprospekting. Penelitian ini dilakukan pada bulan Mei-Juni tahun 2023. Metode penelitian dilakukan dengan cara survei, wawancara, dan analisis vegetasi. Hasil penelitian menunjukkan bahwa masyarakat sebagian besar setuju terkait manfaat ekologi, ekonomi, dan sosial budaya yang dihasilkan dari pemanfaatan lahan menjadi sistem agroforestri sebagai sistem yang berkelanjutan. Terdapat beberapa jenis tumbuhan pada lahan agroforestri memiliki potensi besar untuk dimanfaatkan guna mendukung bioprospekting. Dengan persentase jenis tumbuhan yang memiliki potensi bioprospekting pangan sebesar 37%, untuk obat 37%, dan bahan kosmetika 26%. Melalui pengembangan tanaman bioprospekting, diharapkan mampu membantu masyarakat untuk mengoptimalkan penggunaan lahan pertanian dengan sistem agroforestri. Kata kunci: Agroforestri, Bioprospekting, Skala Likert